2010
DOI: 10.1007/s10644-010-9099-z
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and government spending in Malaysia: a re-examination of Wagner and Keynesian views

Abstract: ARDL bounds approach, Spending on education, GDP growth, Malaysia, Government spending, H52, C22, O23, E62,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
2
16
0
1
Order By: Relevance
“…The policy implication of this finding is that both the short-run and long-run expenditure has a significant effect on economic growth of Nigeria. Also, [12] examine Wagner's law and Keynesian hypothesis in Malaysia by making use of annual data spanning 1970 to 2006. The empirical findings show that within a bivariate and multivariate framework as well as ARDL technique, Wagner's law does not hold in the case of Malaysia in the long-run.…”
Section: Keynesian Hypothesismentioning
confidence: 99%
“…The policy implication of this finding is that both the short-run and long-run expenditure has a significant effect on economic growth of Nigeria. Also, [12] examine Wagner's law and Keynesian hypothesis in Malaysia by making use of annual data spanning 1970 to 2006. The empirical findings show that within a bivariate and multivariate framework as well as ARDL technique, Wagner's law does not hold in the case of Malaysia in the long-run.…”
Section: Keynesian Hypothesismentioning
confidence: 99%
“…Thus, Wagner law was supported in the short run. Meanwhile, Govindaraju et al [12] examines Wagner's law and the Keynesian hypothesis using Auto Regressive Distributed Lag (ARDL) approach to investigate cointegration in Malaysia, using time series data from 1970 to 2006. The analysis revealed that aggregate government spending Granger causes the real GDP, which supports Wagner's law within bivariate framework.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Based on this premise, this study is motivated to investigate the effect of government general spending on human development in Nigeria. Several domestic and foreign studies on government expenditure have been on economic growth (Chandran Govindaraju, Rao & Anwar, 2011;Al-Bataineh, 2012;Gangal & Gupta, 2013;Hasnul, 2015;Al-Shatti, 2014;Lahirushan & Gunsekara, 2015;Torki, 2016;Jelilov & Musa, 2016;Muguro, 2017) among others. Kairo, Mang, Okeke and Aondo (2017) did a similar study in Nigeria, but failed to classify government expenditure into development and nondevelopment in order to determine their specific effect on HDI.…”
Section: Introductionmentioning
confidence: 99%